Ameliorer les performances des perimetres irrigues: Les actes du Seminaire Regional du Projet Management de l'Irrigation au Burkina Faso, 24-26 Juillet 1996, OuagadougouProceedings of regional workshop on performance improvement of irrigation systems, Ouagadougou, Burkina Faso, 24-26 July 1996 - Sally, Hilmy (International Irrigation Management Institute, 1997)
The main purpose of the workshop was to share the results and findings of, and obtain feedback on, the 5 years of work carried out under the IIMI-BF project. The workshop was attended by nearly 70 participants from Burkina Faso, Mali and Niger.